Misinterpretation Of Artificial Intelligence In Arabic Language - Sulaikho, Siti; Munir, Muhammad Syahrul (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Artificial Intelligence is a convenience and problem for students and educators. The purpose of the study was to provide an overview of Artificial Intelligence misinterpretation of Arabic language. This research is descriptive qualitative. The primary source is ChatGPT and the secondary source is Arabic books. The data collection of this research is document and data analysis by means of content analysis. The results showed that Artificial Intelligence can correctly describe theories related to Arabic. But in terms of interpretation, many errors were found. This finding is different from how Artificial Intelligence can interpret other languages more accurately. Therefore, the study of Arabic sourced from Arabic linguists remains the main source. This is due to the unique characteristics of Arabic that are difficult for Artificial Intelligence to detect. The results of this study can be used as a consideration of the use of Artificial Intelligence as a reference in explaining Arabic.